Added value of banana processed products in North Batukliang District, Central Lombok Regency - Mulyawati, Sri; Fernandez, Tajidan F.X. Edy; Efendy, Efendy; Nabilah, Sharfina; Faradila, Jihan Dita (Jurnal Agrotek Ummat, 2025)
Bananas are one of the important commodities produced by Indonesian farmers. These commodities are mostly sold in raw form or as perishable products, resulting in relatively low economic value. The development of a processing industry is important to extend the shelf life of products and increase added value at every stage of the production chain. This study aims to analyse the added value of processed banana products in North Batukliang District. The research approach used is descriptive, with the aim of providing a systematic description of the issues under study. The research objects include banana processing businesses that play a role in creating added value in the region. Respondents were selected using snowball sampling because the population size was not known with certainty. The data were analysed using the Hayami value-added method to obtain comprehensive results. The results showed that banana sale products generated added value of IDR 10,484/kg of raw materials, which was higher than banana chips, which had a value of IDR 3,278/kg of raw materials. The added value ratio generated is 68% for banana chips and 46% for banana chips. These findings indicate that increasing the production of banana chips can be a more profitable strategy for businesses because it provides higher economic added value and supports the development of local agro-industry. This study recommends that businesses increase the scale of banana chip production to optimise profits.